Myanmar Coup and Connections of International Network Terrorism Affiliate in Transnational Legal View - Muhammad Nuha Maulana Pasya; Yeni Widowaty (Faculty of Law, University of Mataram, 2021)
The international community nowadays currently encountering the most serious problem in the face of terrorism. Today, terrorism has destroyed and disrupted the state process. Universally terrorism is the hostist humani generis (the enemy of all mankind). Today terrorism is directed not only against individuals and groups but towards a larger entity, namely the state, and also creates problems and dangers felt by the international community. The variety of terrorist groups is different, from radical issues to political issues. Myanmar is one of the countries in Southeast Asia, and has one of the areas called Rakhine and there are ethnic Rohingya who inhabits the region. Genocide, discrimination, and racial cleansing are three general issues that exist in myanmar. The Myanmar government accuses being terrorists affiliated with international terrorism established due to the butterfly effect of the three things above. The countries in southeast Asia unite themselves and form an international organization called ASEAN, making protection against terrorism that surrounds the southeast Asian region. Therefore, this article was made to find out the cause and countermeasures of terrorism. This research is a normative qualitative approach with a constructive paradigm with the international law